Rising Students’ Cultural Awareness and Listening Skill: How to Use English Movies in EFL Classroom - Nurhuda. H Nurhuda. H (Universitas Lancang Kuning, 2016)
The importance of teaching English culture through media in the EFL classroom has been discusseda lot and widely recognized. How to use English movies to improve a student’s listening and speaking abilityin Indonesian EFL culture learning classrooms. Since a picture is worth a thousand words, many teachers usemovies in their classes. This study conducted in and through the Al-Amin Library at the University ofMuhammadiyah Makassar, over ninety (90) days. Primary searches will be conducted via the Internet throughEBSCO host with ERIC, Academic Search Elite and Google/ Google as the primary sources. Key searchtopics include “culture learning”, “movie”, “EFL”, and “listening”. A brief review of literature on the studiesof culture teaching strategies employed by EFL learners were conducted. A second review of literaturerelating factors include the importance of cultural teaching, why we choose movies to teach, how should theteachers use movies.